ANALISIS USAHATANI PEPAYA VARIETAS CALIFORNIA ANALYSIS OF CALIFORNIA PAPAYA VARIETY FARMING - Meita Yulandari; Rini Purwatiningsih (FORAGRI : Jurnal Ilmu Pertanian, 2023)
Papaya is a herbaceous fruit plant from the Caracecae family and is a horticultural commodity that has high economic value. Increasing public awareness of the importance of this fruit can increase the demand for papaya, so farmers need to analyze California papaya farming. The aims of this study were (1) to determine the income of California papaya farming in Sumber Anom Village, Tamanan District, Bondowoso Regency (2) to determine the efficiency of California papaya farming in Sumber Anom Village, Tamanan District, Bondowoso Regency (3) to determine the factors that influence papaya farming income. California in Sumber Anom Village, Tamanan District, Bondowoso Regency. Data analysis using descriptive statistics. The method used to determine the income of california papaya farmers is by income analysis, which includes R/C Ratio, BEP, Multiple Linear Regression, Data Quality Test, Data Reliability Test, Classical Assumption Test. The average yield of California papaya farmers in Sumber Anom Village, Bondowoso Regency per hectare is 3,187 kg, the average total revenue is Rp. 7,329,333.00, the average total cost incurred is Rp. 2,699,317.00, so that the profit obtained is IDR 4,630,016.00. The efficiency (R/C) value of California papaya farming in Sumber Anom Village, Tamanan District, Bondowoso Regency is 2.74.